2020
DOI: 10.3390/biom10030447
|View full text |Cite
|
Sign up to set email alerts
|

Role of 3-Mercaptopyruvate Sulfurtransferase in the Regulation of Proliferation, Migration, and Bioenergetics in Murine Colon Cancer Cells

Abstract: 3-mercaptopyruvate sulfurtransferase (3-MST) has emerged as one of the significant sources of biologically active sulfur species in various mammalian cells. The current study was designed to investigate the functional role of 3-MST's catalytic activity in the murine colon cancer cell line CT26. The novel pharmacological 3-MST inhibitor HMPSNE was used to assess cancer cell proliferation, migration and bioenergetics in vitro. Methods included measurements of cell viability (MTT and LDH assays), cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 50 publications
2
82
0
Order By: Relevance
“…Moreover, 3-MST silencing in adipocytes was recently reported to increase the extracellular acidification rate [46], while in endothelial cells, 3-MST silencing or HMPSNE decreased various glycolytic parameters [39]. In murine colon cancer cells, HMPSNE exerted a bell-shaped effect on glycolytic parameters (increases at the lowest inhibitor concentration used and decreases at higher concentrations) [14]. Different cell types in culture may rely to a different extent on oxidative phosphorylation vs. glycolysis, and the biochemical mechanisms regulating these processes may also be cell-type different, which may explain the lack of HMPSNE's significant effect on glycolysis in the current study.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, 3-MST silencing in adipocytes was recently reported to increase the extracellular acidification rate [46], while in endothelial cells, 3-MST silencing or HMPSNE decreased various glycolytic parameters [39]. In murine colon cancer cells, HMPSNE exerted a bell-shaped effect on glycolytic parameters (increases at the lowest inhibitor concentration used and decreases at higher concentrations) [14]. Different cell types in culture may rely to a different extent on oxidative phosphorylation vs. glycolysis, and the biochemical mechanisms regulating these processes may also be cell-type different, which may explain the lack of HMPSNE's significant effect on glycolysis in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…To address this question, we employed the recently discovered 3-MST inhibitor HMPSNE, which, to date, is the most potent and most selective pharmacological inhibitor of this enzyme [10,36]. HMPSNE has been successfully employed in cell-based studies in various cell types, at concentrations similar (or higher) [14,[37][38][39] than those used in the current project. Pharmacological inhibition of 3-MST in healthy control fibroblasts only had a slight effect on cellular bioenergetic parameters, but it reduced their proliferation rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that the administration of sublethal concentrations of piperine disrupted classical events related to TGF-β1 induced-EMT processes, such as morphology changes, phenotypic alterations, increased cell motility and expression of metalloproteinases [66,76]. In order to monitor the effect of piperine on cell motility, we initially used the wound assay, a widely used technique [55,[77][78][79]. The results showed that piperine abrogated the increased cell motility induced by TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, several cancer cell lines and tumor specimens have been shown to overexpress one or more of the H 2 S-synthesizing enzymes, including MST, resulting in increased H 2 S levels, which have been proposed to promote carcinogenesis through the regulation of various cancer-related processes [ 97 ]. In the last decade, a novel concept emerged in the field of cancer biology, demonstrating that various cancer cells can increase their endogenous H 2 S levels and use it in an autocrine and paracrine manner to promote cell proliferation, cytoprotective signaling, angiogenesis, and stimulate cellular bioenergetics [ 131 ]. In fact, several biological roles regarding H 2 S in cancer cells have been proposed [ 131 ], which reinforces the importance of the CAT:MST system in cancer context.…”
Section: Role Of the Cat:mst Axis In Cancer Metabolic Remodelingmentioning
confidence: 99%